Prevalence of Multidrug-Resistant Bacteria in Healthcare-Associated Bloodstream Infections at Hospitals in Riyadh, Saudi Arabia - Saeed S. Banawas; Ahmed S. Alobaidi; Turki M. Dawoud; Abdullah AlDehaimi; Faisal M. Alsubaie; Ahmed Abdel-Hadi; Palanisamy Manikandan (Pathogens, 2023)
Bloodstream infection (BSI) prevalence in hospitalized patients has increased owing to the spread of antibiotic-resistant pathogens; moreover, antimicrobial resistance in bacteria is a global problem. Here, BSIs are investigated in several patients at a hospital in Saudi Arabia, and the resistance of bacterial isolates to widely used drugs is determined. Throughout 2020, bacteria isolated from patients were identified and subjected to antibiotic susceptibility testing. In total, 1125 bacterial isolates were obtained from 1039 patients; among them, gram-positive bacteria were significantly more abundant than gram-negative bacteria. The most prevalent bacteria were Staphylococcus epidermidis and Klebsiella pneumoniae. Notably, gram-negative bacteria were mainly isolated from adult patients, and 20.63% of the gram-positive isolates were from pediatric patients, which was significantly higher than the corresponding percentages in elders and adults. The gram-positive isolates were mainly resistant to cephalothin, oxacillin, amoxicillin-clavulanate, and erythromycin and susceptible to penicillin, gentamicin, ciprofloxacin, and vancomycin. Additionally, the gram-negative isolates were mainly resistant to ampicillin, cephalothin, and amoxicillin-clavulanate and susceptible to amikacin, ertapenem, aztreonam, colistin, and trimethoprim-sulfamethoxazole. Consequently, the high prevalence of infective multidrug-resistant bacteria may account as a significant health issue; it is considered a hazard in Riyadh hospitals and must be prevented at all costs.